Systemowość prawa wobec konfliktów społecznych - Bator, Andrzej (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The starting point for the presented text is the general belief in the culture of statutory law assumption made in the study of legal texts, that the law is systemic in character. This view has strongly influenced so far the arguments used in legal disputes. The fundamental question put here is the question whether meta-rules, being a consequence of the thesis on the systemic character of law, may be reasonably in a manner acceptable to the parties applied to such legal disputes, which may be qualified also as political conflicts. The answer is positive, yet under certain condition: “systemic character” trait, raised by analytical theories of law, should be used only in so-called “easy cases”, as “hard cases” inevitably belong to a competitive domain of so-termed “political philosophy”. This could imply a significant narrowing of the scope of application of some theorems belonging to these trends in the field of analytical legal theory, which have been dominant in the Polish legal thought. This includes mainly claims connected with the so-called “deep structure of legal science”, eg. a theorem of rationality of the lawgiver.
Keywords: system prawa; konflikty społeczne